Avtomatiziran video nadzor Centra za preprečevanje in zdravljenje odvisnosti od prepovedanih drog v Trbovljah - Ikica, Branko (Informatica Medica Slovenica, 2003)
Among many public institutions, violence and criminal rate are also rapidly spreading to those dealing with a drug abuse and drug addiction problems. Working staff in such centres is quite often exposed to violence, so a good video surveilance system is of main concern to them. In this article we present an automated video surveillance system installed in "Centre for drugs and drug addiction"' in Trbovlje (Slovenia). Among many other options it allows a fully automated video surveilance of centre and duick overview of centre's headquaters.
Keywords: elektronski nadzor; javne ustanove; nadzor; Rehabilitation; Snov, zloraba, centri za zdravljenje; Substance Abuse Treatment Centers; Substance Dependence; video nadzor; Video Recording; Video snemanje